Green Energy Transformation In Sumatera: The Influence Of Government Expenditure On The Achievement Of Sdg 7 (Clean And Affordable Energy) - Rizal, Moch Rifqi; Hidayatullah, Firda (Indonesian Scientific Publication, 2024)
This research aims to explore government expenditure's impact on achieving SDG 7 (Affordable and Clean Energy) in Sumatera. The primary focus of this study is on green energy transformation as a strategic effort to enhance economic growth and societal well-being in the region. Using quantitative methods, this research analyzes secondary data from various sources, including government expenditure reports and statistical data related to the achievement of SDG 7. The findings indicate that government spending in the energy sector, particularly in infrastructure and services, significantly impacts achieving clean and affordable energy targets. However, challenges such as insufficient infrastructure and suboptimal regulations remain major obstacles. This study provides critical insights for policymakers in designing more effective strategies to accelerate green energy transformation in Sumatera and support the national achievement of SDG 7 targets.